An unusual presentation of diabetic amyotrophy: myoclonus. (4th February 2013) - Zaidi, Syed Amir; Chhetri, Suresh Kumar; Lekwuwa, Godwin; Majeed, Tahir
Abstract : Diabetic amyotrophy is a distinctive form of diabetic neuropathy. It is characterised by a weakness and wasting of proximal muscles of the lower limbs with associated pain. We report a case of an elderly patient with unusual presentation of diabetic amyotrophy. He presented with myoclonic jerks and recurrent falls. Examination findings and electrophysiological studies were consistent with a diagnosis of diabetic amyotrophy. He responded well to steroids with marked improvement in strength of the lower limb muscles and complete resolution of myoclonic jerks. Diabetic amyotrophy presenting as myoclonic jerks has been rarely reported before.